PREVALENCE AND CHARACTERISTICS OF RESISTANT HYPERTENSIVES IN A GREEK POPULATION. (June 2018) - Andreadis, E.; Georgantoni, A.; Geladari, C.; Savva, F.; Apeiranthiti, K.; Pantikidi, E.; Papakonstantinou, I.
Abstract : Objective: Resistant hypertension (RH) is a common problem encountered in clinical practice and obscures to the uncontrolled office hypertension. We investigated subjects with controlled (<140/90 mmHg) and uncontrolled (>/ = 140/90 mmHg) office blood pressure (OBP) on three drugs, one of those being a diuretic. Design and method: Blood pressure (BP) was measured twice in the office with a validated oscillometric device, after a 5-min rest period in a sitting position, on two consecutive visits. Consequently, all participants underwent 24 h ambulatory blood pressure monitoring (24h-ABPM), using the Microlife O3 Afib device, programmed to record BP at 20 min intervals for the 24 h period, so as to segregate those with pseudo- and true RH (tRH) and distinguish the clinical and laboratory differences among them. Data are presented as frequencies and percentages for qualitative variables and as mean ± SD for quantitative variables. Results: A total of 162 individuals, mean age 63.54 ± 10.41 years, 71 women were included in the analysis. Of those, 54 (33.3%) were controlled in the office, in contrast to 108 (66.7%) who remained uncontrolled. Specifically, 40 (24.7%) had tRH with OBP > 140/90 mmHg and 24h-ABPM > / = 130/80 mmHg, 68 (42%) had pseudoresistance or white coat effect (WCE), with OBP > / = 140/90 mmHg and 24h-ABPM < 130/80 mmHg. Likewise, 11 (6.8%) participants had office BP controlled and 24h-ABPM uncontrolled (masked uncontrolled hypertensives, MUH). WCE and MUH reached of 48.8% of the whole population. tRH was prominent among younger males (p 0.013 and 0.042, for age and sex, respectively). Furthermore, subjects with tRH had higher mean OBP values (p < 0.001). They also had higher frequency of dyslipidemia (p < 0.05) and diastolic dysfunction (p < 0.001), compared to the other groups. In contrast, pseudoresistants had more frequently carotid plaques (p < 0.05). Masked RH was most commonly observed among smokers (p < 0.05). Conclusions: MUH and WCE constituted a large proportion of the studied population. Moreover, subjects with tRH had a higher likelihood of diastolic dysfunction that may be due to the higher BP values, whereas pseudoresistants exhibited frequently carotid atherosclerosis.